Предмет: Алгебра,
автор: tema0love
Представьте в виде произведения:
2m(n-n)+m-n=
4p(p+1)+p+1=
a(x-c)+bc-bx=
Ответы
Автор ответа:
0
.........................
Приложения:
Автор ответа:
0
2m(n-n)+m-n= 2mn-2mn+m-n= m-n
4p(p+1)+p+1=4p2+ 4p+p+1= 4p2+5p+1=p(4p+5)+1
a(x-c)+bc-bx=ax-ac+bc-bx= a(x-c)+b(c-x)= (c-x)(a+b)
4p(p+1)+p+1=4p2+ 4p+p+1= 4p2+5p+1=p(4p+5)+1
a(x-c)+bc-bx=ax-ac+bc-bx= a(x-c)+b(c-x)= (c-x)(a+b)
Приложения:
Похожие вопросы
Предмет: Химия,
автор: fdff123
Предмет: Физика,
автор: Аноним
Предмет: Математика,
автор: lera13579059
Предмет: Алгебра,
автор: Марал
Предмет: История,
автор: vlada2001